PENINGKATAN HASIL BELAJAR TOLAK PELURU MELALUI PENERAPAN STRATEGI PEMBELAJARAN RESIPROKAL MAN 2 MODEL MEDAN - Syahputra, Irawan; Bangun, Sabaruddin Yunis (Journal Physical Education, Health and Recreation, 2018)
This study aims to determine the improvement of the learning outcomes learning process by applying the reciprocal learning strategy in the students of class XII MAN 2 Model Medan Year 2017. This study was conducted on the students of class XII IPA1 who became the subject with a total of 36 students. The method used in this research is Classroom Action Research. The indicator of research success is the application of reciprocal learning strategy in accordance with the referenced syntax. Student activities have the same task in accordance with the ability and ability of learners can improve learning outcomes. From the results of data analysis can also be known that the learners learn from the initial test and test results of learning I still low. It is therefore necessary to improve the action for cycle II. The second cycle of teachers improves and motivates to be more active in the repetition at the implementation stage and its follow-through. The study concluded: In the first cycle of 36 students there were 20 students (55.5%) who had reached the completeness of learning, while 16 students (44.5%) have not achieved complete learning. With the average score of students learning outcomes is 61.1. While on the second cycle can be seen that the ability of learners in doing the test results of learning cycle II has been increasingly classical. Of the 36 students there were 33 people (91.6%) who had achieved complete learning, while 3 students (8.4%) had not yet achieved complete learning. With the average score of students learning outcomes is 71.25.